A metamorfose da questão do imperialismo nas configurações contemporâneas do Sistema do Capital - Melo, Aquiles Chaves de (2011)
Some authors note the disappearance of the term "imperialism" of contemporary political debates. This concept returns to the scene especially with the American entry into the Iraq war and Bush proclaimed fight against terrorism. However its meaning no longer holds any relationship to the economic basis of social structure, now being used in their conception of the nineteenth century, where it was seen as a great civilizing mission. What we perceive is that the various attempts to extinguish the concept of i mperialism were not fruitful for the interpretation of the dynamic reality of contemporary capitalism. Our hypothesis is that the maintenance of the international monetary system today, in the form of the floating dollar standard, creates an environment hi ghly conducive to the reproduction of capital by the hegemonic nation, where the United States, through the appropriation of the wealth of the peripheral countries , becoming the core of the contemporary imperialist nature.